Mechanism-based myofilament manipulation to treat diastolic dysfunction in HFpEF - Katherine L. Dominic; Alexandra V. Schmidt; Henk Granzier; Kenneth S. Campbell; Kenneth S. Campbell; Julian E. Stelzer (Frontiers in Physiology, 2024)
Heart failure with preserved ejection fraction (HFpEF) is a major public health challenge, affecting millions worldwide and placing a significant burden on healthcare systems due to high hospitalization rates and limited treatment options. HFpEF is characterized by impaired cardiac relaxation, or diastolic dysfunction. However, there are no therapies that directly treat the primary feature of the disease. This is due in part to the complexity of normal diastolic function, and the challenge of isolating the mechanisms responsible for dysfunction in HFpEF. Without a clear understanding of the mechanisms driving diastolic dysfunction, progress in treatment development has been slow. In this review, we highlight three key areas of molecular dysregulation directly underlying impaired cardiac relaxation in HFpEF: altered calcium sensitivity in the troponin complex, impaired phosphorylation of myosin-binding protein C (cMyBP-C), and reduced titin compliance. We explore how targeting these pathways can restore normal relaxation, improve diastolic function, and potentially provide new therapeutic strategies for HFpEF treatment. Developing effective HFpEF therapies requires precision targeting to balance systolic and diastolic function, avoiding both upstream non-specificity and downstream rigidity. This review highlights three rational molecular targets with a strong mechanistic basis and potential for therapeutic success.